Knowledge creation : a study of consulting practice in corporate governance : a thesis presented in partial fulfilment of the requirements for the degree of Master of Management at Massey University, Palmerston North, New Zealand - Peirano-Vejo, Maria Elisa (Massey University. Department of Management, 2004)
The management consulting industry has been growing exponentially during the last two decades influencing the relationships between business schools, corporations and universities, achieving a significant role as a modern "knowledge creator". This thesis studies the process of knowledge creation undertaken by management consultants. The academic mode of creating knowledge as described by Kuhn (1996) was used to direct this exploration of consultants as a knowledge creating community. The purpose of using the scientific method of knowledge creation is not to compare or to judge consulting knowledge, but to use it as a way of entry to explore consultants' practices. In a complementary way to Kuhn's core concepts, a brief Foucauldian overview identified concepts like inclusion and exclusion, discourse and the notion of practices, which are used in the analysis. An empirical research was conducted focusing specifically on a group of practicing consultants in New Zealand. Thirteen consultants who specialize in corporate governance advice were interviewed. Corporate governance was chosen as a field of advice because it is a clearly separable area of management consulting. In this study, the categories of community and paradigm served as a point of entry to explore knowledge creation practices. The data was analyzed qualitatively in search for evidence of community belonging and patterns in consultants' knowledge creation practices. It has been found that consultants, in spite not having a formal regulating professional body, behave as a professional community that has entry requirements, exit procedures and credentials for belonging. Consultants define their identities in the intersection of overlapping communities, which sometimes include their former educational backgrounds, their professions and their current practice. Research findings show that consultants in governance share a paradigm, which trascend particular consulting firms and reach a larger group of consultants. This paradigm has quality control processes such as reputation and re-engagement, and common methods in dealing with governance problems. In addition, in terms of the body of knowledge shared, there are certain factors that determine the value of that knowledge for consultants such as novelty, commercial value, utility and accessibility.
Keywords: Consultants; Knowledge; Corporate governance; Management consulting; Consultants; Thomas Kuhn; 350200 Business and Management